A Comparison between the Strep a Rapid Test Device and Conventional Culture for the Diagnosis of Streptococcal Pharyngitis. Issue 4 (1st August 2006) - Forward, Kevin R; Haldane, David; Webster, Duncan; Mills, Carolyn; Brine, Cheryl; Aylward, Diane
Abstract : BACKGROUND: Rapid antigen detection tests are frequently used to diagnose pharyngitis due to Streptococcus pyogenes . Because a large number of kits are available commercially, performance characteristics may vary considerably. The present study evaluated one such kit currently in use in Canadian laboratories for which published evaluations are not available. OBJECTIVE: To evaluate the performance characteristics of the Strep A Rapid Test Device (SARTD) (Nova Century Scientific Inc, Canada). METHODS: Pharyngeal swabs from 818 patients with suspected streptococcal pharyngitis were tested. Swabs were initially inoculated onto the surface of a blood agar plate and then used to perform the rapid antigen test. The test was performed in accordance with the product monograph. Beta-hemolytic colonies were identified as S pyogenes using conventional means. RESULTS: Four hundred ninety specimens were obtained from children and 328 from adults. S pyogenes was recovered from 171 (21%) patients. The SARTD detected S pyogenes antigens in 123 of 171 specimens from which S pyogenes was isolated on culture; the screen was negative in 610 of 647 specimens from which cultures were negative. The positive and negative predictive values of the SARTD were 76.9% and 92.7%, respectively. CONCLUSIONS: The SARTD was much less sensitive (72%) than was suggested in the product monograph (90%). Laboratories should vigorously evaluate such products in-house, optimize specimen collection and transport, and choose more sensitive kits for use.